GAYA KEPEMIMPINAN DEMOKRATIS TRANSFORMATIF GURU TERHADAP MANAJEMEN PEMBELAJARAN KELAS - Deviana, Marliza; Giatman, M.; Yuliarma, Yuliarma; Mardizal, Jonni (Jurnal Manajemen Pendidikan, 2025)
This study aims to determine the effect of teachers' democratic-transformative leadership style on classroom learning management at SMK Negeri 7 Sijunjung. The background of this study is based on the importance of the role of teachers as learning leaders who are able to inspire, actively involve students, and create a participatory and conducive learning atmosphere. This study uses a quantitative approach with descriptive methods and correlational analysis. The research sample consisted of 41 grade X students, 23 grade XI students, and 10 teachers in the Computer and Network Engineering (TKJ) Expertise Concentration. Data collection was carried out through questionnaires and field observations. The results of the analysis show that teachers' democratic-transformative leadership style is in the very good category with an average score of 4.25, while classroom learning management obtained an average score of 4.20. The Pearson correlation test produced a value of r = 0.712 (p = 0.000), which means there is a positive and significant relationship between the two variables. The determination value (R²) of 0.507 indicates that 50.7% of the effectiveness of classroom learning management is influenced by teachers' leadership style. Thus, the better the implementation of democratic-transformative leadership, the more effective the management of learning in the classroom.